MANAGEMENT TECHNIQUES FOR IMPROVING THE QUALITY OF DECISION-MAKING BY OWNERS OF APARTMENT BUILDINGS ON THE CHOICE OF MANAGEMENT ORGANIZATION - A. V. Demin; I. V. Rybalchenko; I. V. Milkina (Вестник университета)
The procedure for choosing the organization managing the apartment building is regulated in detail by legislation. However, the law, formally conforming to market principles, leaves the owners of residential premises in the house without any reasonable selection criteria. The wrong choice of a management company is fraught not only with economic losses, but also with safe living. At the same time, the ratings proposed for state accounting or statistics cannot be applied by owners to select the best candidate, since they have other goals. The limited applicability of these ratings and criteria systems has been argued in the article, and also well-grounded approaches and a new system of criteria necessary to resolve the selection problem have been proposed.